PH‐Responsive Relaxometric Behaviour of Coordination Polymer Nanoparticles Made of a Stable Macrocyclic Gadolinium Chelate. Issue 37 (4th August 2016) - Aríñez‐Soriano, Javier; Albalad, Jorge; Carné‐Sánchez, Arnau; Bonnet, Célia S.; Busqué, Félix; Lorenzo, Julia; Juanhuix, Jordi; Terban, Maxwell W.; Imaz, Inhar; Tóth, Éva; Maspoch, Daniel
Abstract: Lanthanide‐containing nanoscale particles have been widely explored for various biomedical purposes, however, they are often prone to metal leaching. Here we have created a new coordination polymer (CP) by applying, for the first time, a stable Gd III chelate as building block in order to prevent any fortuitous release of free lanthanide(III) ion. The use of the Gd‐DOTA‐4AmP complex as a design element in the CP allows not only for enhanced relaxometric properties (maximum r 1 =16.4 mm −1 s −1 at 10 MHz), but also for a pH responsiveness (Δ r 1 =108 % between pH 4 and 6.5), beyond the values obtained for the low molecular weight Gd‐DOTA‐4AmP itself. The CP can be miniaturised to the nanoscale to form colloids that are stable in physiological saline solution and in cell culture media and does not show cytotoxicity. Abstract : An act of Gd : A coordination polymer has been synthesised by using a stable Gd III chelate in order to prevent any fortuitous release of free lanthanide ion. The use of this chelate as a linker in the coordination polymer allows the enhancement of the relaxometric properties (maximum r 1 =16.4 mm −1 s −1 at 10 MHz) and the pH responsiveness (Δ r 1 =108 % between pH 4 and 6.5), beyond the values obtained for the Gd III chelate itself.